The effect of steroid injection into the shoulder on glycemia in patients with type 2 diabetes - Ori Safran, MD; Gabriel Fraind-Maya, MD; Leonid Kandel, MD; Gil Leibowitz, MD; Shaul Beyth, MD, PHD (JSES International, 2022)
Background: Injections of corticosteroids into or around joints have been reported to increase blood glucose in patients with diabetes due to corticosteroid absorption into the bloodstream. However, the magnitude, duration, and clinical implications of local corticosteroid injections on glycemic control are not clear. The purpose of this study was to evaluate the effects of corticosteroid injection to the shoulder on glycemia in patients with type 2 diabetes mellitus using a continuous glucose monitoring device. Methods: Twenty-five patients with symptomatic shoulder problems and type 2 diabetes mellitus, not treated with insulin, prescribed a corticosteroid injection into the shoulder, were investigated. The patients were connected to a flash glucose monitoring system, which continuously monitored interstitial glucose levels. Data were collected 3 days before injection and for additional 11 days after corticosteroid injection. We analyzed glucose levels in the first 3 days (early postinjection) and on days 4-11 (late postinjection) after the injection and compared them to the preinjection period. The outcome measures included change in the average glucose levels, per patient, between the preinjection and postinjection periods and the differences in the time spent at glucose >180 mg/dL, >250 mg/dL, and >350 mg/dL, per patient, between the preinjection and postinjection periods. Results: The increase in the mean glucose level per patient was statistically significant from 136 mg/dL in the preinjection period to 159 mg/dL in the first 3 days after the injection and returned to normal thereafter. Time at blood glucose >250 mg/dL increased from 4.3% in the preinjection period to 9.5% on the first day after the injection. It then decreased to 7% on day 2, 3.8% on day 3, and 1.4% in the late postinjection period. New onset of glucose levels >350 mg/dL was found in 4 of 25 patients during the early postinjection period. In all 4 patients, the exposure to severe hyperglycemia (>350 mg/dL) was short. None of the patients required intensification of the antidiabetic treatment or insulin injections. Conclusion: Local corticosteroid injection to the shoulder can create a significant, short-term increase in systemic glucose levels in patients with D2DM not treated with insulin. Some of these patients may have periods with glucose above 350 mg %. However, these glycemic changes are short lived and are mostly limited to the 2-3 days after the injection. In addition, none of the patients in our study needed any change in antidiabetic treatment or any medical care after the injection.